Military Expenditure and Economic Growth in South Asian Countries: Empirical Evidences - Ismail, Saba (International Journal of Economics and Financial Issues, 2017)
This paper is an attempt to examine the relationship between military expenditure and economic growth in South Asia region. Panel fixed effect model has been estimated using panel data from five South Asian Countries. The results indicate positive effect of military expenditure on economic growth but significantly less compared to alternative uses of scare resources as non-military expenditure. This study raises an important issue of huge opportunity cost of military expenditure and foregone opportunity of economic growth. The paper concludes that the boosting of economic growth through higher military expenditure is neither effective nor efficient way of achieving higher growth. Keywords: Military expenditure; Economic growth; Panel Data, South Asia JEL Classifications: H5, O41, O47